2021
DOI: 10.3390/math9141698
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Efficiency Study of Output Lubricant Flow Rate Regulating Principle on the Example of a Two-Row Aerostatic Journal Bearing with Longitudinal Microgrooves and a System of External Combined Throttling

Abstract: Due to their vanishingly low air friction, high wear resistance, and environmental friendliness, aerostatic bearings are used in machines, machine tools, and devices that require high accuracy of micro-movement and positioning. The characteristic disadvantages of aerostatic bearings are low load capacity, high compliance and an increased tendency for instability. In radial bearings, it is possible to use longitudinal microgrooves, which practically exclude circumferential air leakage, and contributes to a sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The characteristic polynomial of the TF (48) can be reduced to the form of the polynomial (47) by multiplying the first by the constant b 0 . Studies of adaptive slip bearings show that the sign of static compliance is determined by the coefficient b 0 [18,19]. In this case, the coefficients of the denominator polynomial for stable systems always remain positive, which indicates the stability of such dynamical systems.…”
Section: Some Considerations Regarding the Methodology For Applying T...mentioning
confidence: 99%
See 1 more Smart Citation
“…The characteristic polynomial of the TF (48) can be reduced to the form of the polynomial (47) by multiplying the first by the constant b 0 . Studies of adaptive slip bearings show that the sign of static compliance is determined by the coefficient b 0 [18,19]. In this case, the coefficients of the denominator polynomial for stable systems always remain positive, which indicates the stability of such dynamical systems.…”
Section: Some Considerations Regarding the Methodology For Applying T...mentioning
confidence: 99%
“…Studies have shown that the inflow of additional energy contributes to a significant deterioration in the dynamic quality of the structure up to the loss of stability [15,16]. It is possible to improve the dynamics of the bearings due to the complication of the design through the use of an external combined throttling system (ECTS) whereby an additional hydraulic resistance is installed between the bearing gap and the regulator, which makes it possible to put in place an inter-throttle chamber, the volume of lubrication of which acts as a viscous damper for energy dissipation [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…With regard to fluid lubrication, numerical methods such as the finite difference method are frequently adopted to solve the simplified Reynolds lubrication equation [29][30][31][32]. The above method is easy to apply to bearings with simple shapes, as inertial and radial flow are ignored.…”
Section: Introductionmentioning
confidence: 99%